EXC!TE SNARE DRUM — Making an Audio Plugin with Pure Data inside - Neupert, Max; Wegener, Clemens; Schmalfuß, Philipp; Stang, Sebastian (Revista Vórtex, 2021)
This report describes how we made a VST3 plugin containing Pure Data and integrated libpd into VCV Rack, iPlug2 and the VST3SDK. The plugin is a real-time snare drum synthesizer using an exciter-resonator model. We discovered an undesirable effect in Pd where the computationally cheap 4-point interpolation on delread4~ creates audible artefacts, effecting our wave-guide. Our solution to this issue was to implement our own interpolation object based on advice from Cyrille Henry posted to the Pd mailing list in 2008. The implementation was taken from Julius O. Smith's Digital Audio Resampling reference book.